2006
DOI: 10.1158/0008-5472.can-05-2216
|View full text |Cite
|
Sign up to set email alerts
|

Expression of p53 Enhances Selenite-Induced Superoxide Production and Apoptosis in Human Prostate Cancer Cells

Abstract: Although the anticancer effects of selenium have been shown in clinical, preclinical, and laboratory studies, the underlying mechanism(s) remains unclear. Our previous study showed that sodium selenite induced LNCaP human prostate cancer cell apoptosis in association with production of reactive oxygen species, alteration of cell redox state, and mitochondrial damage. In the present study, we showed that selenite-induced apoptosis was superoxide mediated and p53 dependent via mitochondrial pathways. In addition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
72
1
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 99 publications
(89 citation statements)
references
References 47 publications
15
72
1
1
Order By: Relevance
“…5A, transfection of p53 siRNA suppressed SeMet-plus METase-induced elevation of superoxide, although p53 siRNA transfection alone also increased levels of superoxide compared with the control. The latter was most likely due to superoxide production from RNAiFect and siRNA transfection, which was observed in our previous study (8). Conversely, reexpression of wt p53 in PC3 cells significantly increased superoxide production following SeMet and METase treatment (Fig.…”
Section: P53-dependent Superoxide Production By Semet Plus Metasetreasupporting
confidence: 72%
See 2 more Smart Citations
“…5A, transfection of p53 siRNA suppressed SeMet-plus METase-induced elevation of superoxide, although p53 siRNA transfection alone also increased levels of superoxide compared with the control. The latter was most likely due to superoxide production from RNAiFect and siRNA transfection, which was observed in our previous study (8). Conversely, reexpression of wt p53 in PC3 cells significantly increased superoxide production following SeMet and METase treatment (Fig.…”
Section: P53-dependent Superoxide Production By Semet Plus Metasetreasupporting
confidence: 72%
“…Flow Cytometric Analysis Cell samples were prepared and analyzed as described previously (8). After trypsinization, 1 Â 10 6 cells were washed with PBS/EDTA/bovine serum albumin buffer (PBS, 1 mmol/L EDTA, 0.1% bovine serum albumin) and fixed in 100 AL of PBS/EDTA/bovine serum albumin buffer plus 900 AL of 70% ethanol for 30 min at À20jC.…”
Section: Chemicals and Antibodiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have demonstrated that the superoxide production in mitochondria is a key event during selenite-induced apoptosis process (18)(19)(20)(21). However, the molecular mechanism of how sodium selenite triggers the accumulation of superoxide remains to be determined.…”
Section: Discussionmentioning
confidence: 99%
“…This phenomenon leads to a decrease in the Bcl-2:Bax ratio, a release of cytochrome-c and the activation of mitochondrial apoptosis (107)(108)(109)(110)(111). Furthermore, two methylselenol precursors, mSeA and Semet, have also been found to decrease the ratio of these pro-apoptotic and anti-apoptotic protein expression levels.…”
Section: Apoptotic Targets Nuclear Factor-Îș B (Nf-Îșb) Pathwaymentioning
confidence: 99%